"They are not HIV treatments drugs; they are preventive drugs (PrEP)". Experiences of PrEP uptake among vulnerable adolescent girls and young women in Tanzania. - Magreth Thadei Mwakilasa; Alexander Mwijage; Stella Mushy; Maryam Amour; Nathanael Sirili; Evaline Maziku; Samwel Likindikoki; Emmanuel Balandya; Gideon Kwesigabo; Benson Kidenya; Stephen E Mshana; Eligius Lyamuya; et al. (PLoS ONE)
Introduction HIV poses a significant global health concern, affecting adolescents among other populations. This is attributed to various vulnerabilities including biological factors, gender inequalities and limited access to comprehensive sexual and reproductive health services in sub-Saharan Africa. In Tanzania, adolescent girls, and young women (AGYW) face double the risk of HIV infection compared to their male counterparts. The introduction of pre-exposure prophylaxis (PrEP) in early 2018 brought hope for changing the HIV cascade in the country. However, numerous challenges still hinder PrEP uptake. Therefore, this study explored experiences of PrEP uptake among vulnerable AGYW in Tanzania. Methods This study employed a phenomenological qualitative approach; 52 semi-structured interviews were carried out between May to November 2022 in the selected healthcare facilities in Tanzania. The study adopted inductive-deductive thematic analysis guided by the Social Ecological Model (SEM) to elicit the views of AGYW aged 15-24. Nvivo software was utilised to organise data. Results This study has uplifted barriers and facilitators on PrEP uptake among AGYW in Tanzania. The barriers are categorized at individual, interpersonal, and institutional levels. The individual level barriers included pre-requisites for initiating PrEP, disbelief in the effectiveness of PrEP, interference of refill hours with working hours, financial constraints, and adherence to the pills. The interpersonal level barriers included misconceptions about PrEP pills, and labelling of PrEP users. The institutional level barriers included inadequate privacy, PrEP drug stockout, being turned away by health care facilities (HCF), long waiting times, and distance to the HCF. Facilitators included factors at individual level (experienced benefit of PrEP, adequate PrEP knowledge, having multiple partners, perceived risk due to the nature of the work, PrEP ensuring privacy), interpersonal level (support from social networks), and institutional level (Free availability of PrEP, receiving refill reminders). Conclusions To overcome barriers to PrEP uptake among AGYW, it is crucial to develop multi-level interventions that consider personal, social, and structural factors hindering PrEP uptake. Implementing strategies like prioritizing off-site PrEP delivery and expanding community outreach for PrEP awareness can help dispel misconceptions and enhance uptake.